At Home With Medical Anthropology in the Former Yugoslavia: Between Socialist Legacies and Neoliberal Realities - Bukovčan, Tanja (Svetovi (Ljubljana), 2026)
The article traces the development of medical anthropolog y in the former Yugoslav region, highlighting how the discipline has evolved through the legacies of social medicine and socialist self-management and, in recent decades, as a response to neoliberal trends in healthcare. The authors understand this region as a site of epistemic resistance and creativ-ity, where scholars respond to shifting healthcare landscapes by rethinking the boundaries between critique and care, theory and practice. Drawing on a wealth of regional references and field experiences, the article offers both a historical and conceptual grounding for this special issue of Svetovi/Worlds, framing medical anthropolog y in the Balkans as simultane-ously local and transnational, reflexive and politically engaged.
Keywords: Antropologija; dediščina socializma; Etnologija; former Yugoslavia; Gospodarski liberalizem; healthcare; historical reviews; Javno zdravje; legacy of socialism; medical anthropology; Medicinska antropologija; nekdanja Jugoslavija; neoliberalism; neoliberalizem; Samoupravljanje; simpoziji; social medicine; socialist self-management; socialistično samoupravljanje; Socializem; Socialna medicina; symposiums; zdravstvo; zgodovinski pregledi